Study of the effects of 0.15 terahertz radiation on genome integrity of adult fibroblasts. (30th March 2018) - Franchini, Valeria; De Sanctis, Stefania; Marinaccio, Jessica; De Amicis, Andrea; Coluzzi, Elisa; Di Cristofaro, Sara; Lista, Florigio; Regalbuto, Elisa; Doria, Andrea; Giovenale, Emilio; Gallerano, Gian Piero; Bei, Roberto; et al.
Abstract : The applications of Terahertz (THz) technologies have significantly developed in recent years, and the complete understanding of the biological effects of exposure to THz radiation is becoming increasingly important. In a previous study, we found that THz radiation induced genomic damage in fetal fibroblasts. Although these cells demonstrated to be a useful model, exposure of human foetuses to THz radiation is highly improbable. Conversely, THz irradiation of adult dermal tissues is cause of possible concern for some professional and nonprofessional categories. Therefore, we extended our study to the investigation of the effects of THz radiation on adult fibroblasts (HDF). In this work, the effects of THz exposure on HDF cells genome integrity, cell cycle, cytological ultrastructure and proteins expression were assessed. Results of centromere‐negative micronuclei frequencies, phosphorylation of H2AX histone, and telomere length modulation indicated no induction of DNA damage. Concordantly, no changes in the expression of proteins associated with DNA damage sensing and repair were detected. Conversely, our results showed an increase of centromere‐positive micronuclei frequencies and chromosomal nondisjunction events, indicating induction of aneuploidy. Therefore, our results indicate that THz radiation exposure may affect genome integrity through aneugenic effects, and not by DNA breakage. Our findings are compared to published studies, and possible biophysical mechanisms are discussed. Environ. Mol. Mutagen. 59:476–487, 2018. © 2018 Wiley Periodicals, Inc.